Serum calcium levels in newly detected essential hypertensive patients - Aashish, Arumugam; Kannaiyan, Jayasingh (International Journal of Advances in Medicine, 2021)
Background: Systemic hypertension is global disease responsible for significant mortality and morbidity. Essential or primary hypertension accounts for the majority of people with hypertension. Although our understanding of the pathophysiology of essential hypertension has grown a lot, its aetiology still remains hypothetical. Few studies in literature have found some correlation with serum calcium levels and blood pressure of the individuals. Methods: A total 200 patients, 100 newly diagnosed essential hypertensive and 100 normotensive patients were included in the study. A detailed history and clinical profile was taken. Blood sample was collected and serum calcium, serum albumin were determined and corrected calcium was calculated and the results were tabulated and appropriate statistical analysis was done. Results: The mean total serum calcium and corrected calcium levels were significantly lowered in essential hypertensive compared to the normotensive individuals. There was no correlation between total serum and corrected calcium levels against systolic and diastolic blood pressure. There was also no difference in serum total and corrected calcium levels among different subsets in essential hypertensive group. Conclusion: Essential hypertension still remains the most common form of hypertension present worldwide causing significant mortality and morbidity. Despite increased advances in medicine and large number of studies done in context with the cause of essential hypertension, its aetiology still remains hypothetical. Even though studies have shown some correlation of calcium fractions with hypertension, the aetiology is still unclear.